Data on cecal and fecal microbiota and predicted metagenomes profiles of female mice receiving whole flaxseed or its oil and secoisolariciresinol diglucoside components - Amel Taibi; Michelle Ku; Zhen Lin; Giorgio Gargari; Alla Kubant; Dion Lepp; Krista A. Power; Simone Guglielmetti; Lilian U. Thompson; Elena M. Comelli (Data in Brief, 2021)
Dietary flaxseed (FS) and its components including FS oil (FSO), secoisolariciresinol diglucoside (SDG) and fiber, are processed by the gut microbiota. These data are in support of the article entitled “Discriminatory and cooperative effects within the mouse gut microbiota in response to flaxseed and its oil and lignan components”, Journal of Nutritional Biochemistry [1]. Here we describe data generated by 16S rRNA sequencing of DNA obtained from cecum contents and feces of C57BL/6 female mice fed either a basal diet (BD, AIN93G), or isocaloric diets containing 10% FS, or 10% FS-equivalent amounts of FSO or SDG for 21 days. These include bacterial community composition and inferred KEGG pathways; the raw data are publicly available at the NCBI SRA database (BioProject ID PRJNA683934). Furthermore, this work includes detailed experimentation procedures, total bacterial counts (qPCR) in the cecum content and feces, and correlation analysis between a selected bacterial genus, Bacteroides and a predicted metabolic pathway. FS is utilized worldwide, especially for the prevention and/or treatment of diseases including cardiovascular diseases, diabetes and cancer. These data will be valuable as a reference to study different FS cultivars and SDG- or FSO- enriched products on the gut microbiota, to study gut microbial responses to FS and its components in different mouse strains and mammalian hosts to elucidate individualized effects, and to understand the importance of the gut microbiota for FS benefits.